Aerosol treatment abuse. Issue 1 (January 1988) - O'Callaghan, C; Milner, A D
Abstract : A 4 year old boy with excellent inhaler technique was found to be abusing his salbutamol and beclomethasone dipropionate inhalers. This resulted in aggressive behaviour and probable hallucinations.